HUMAN CAPITAL VERSUS THE SIGNALING HYPOTHESES: THE CASE OF INDONESIA - Nenny Hendajany; Tri Widodo; Eny Sulistyaningrum (Faculty of Economics and Business, Universitas Gadjah Mada, 2016)
Education positively affects a person's income. It can be explained in two ways. Firstly, education directly increases the productivity of a person, which is in accordance with the views of the theory of human capital. The second way is an indirect effect, in which education acts as a sign (signal) of a worker’s unobserved characteristics, as assessed by an employer who is considering hiring the person. This is consistent with the view of the signaling theory. Both views are often debated in literature. This paper examines the returns to education in Indonesia, separating out the credential effects from the pure years of schooling effects. We used survey data from the Indonesian Family Life Survey (IFLS) 2000, 2007, and 2014 to test the difference of the two theories in estimating the returns to education in Indonesia. This study used three models which consisted of the human capital model, the signaling model, and the hybrid model. The human capital model used the number of years of schooling as a variable representing education, the signaling model used dummy variables from the level of education achieved (elementary school, junior high school, senior high school, diploma, university), and the hybrid model combined both measures of the variables. The hybrid model allows for the separation of the impact of human capital based on an additional year of schooling, and the impact of signaling by the accomplishment of a particular certificate. The results of the study provide strong evidence of the presence of the returns to education either through the human capital or the signaling theories. Keywords: education, human capital, signaling, returns to education